Thermomechanical properties of shape memory epoxy filled nanoclay / carbon Nanotube hybrid composites for aircraft morphing wing application - Mat Yazik, Muhamad Hasfanizam (2020)
Shape memory material is a smart material that can be programmed to a temporary shape and recovered its permanent shape when stimulated. Utilising the shape memory polymer for aerospace structure application such as morphing wing is a promising concept due to its versatility and functionality. However, pure shape memory polymer has a lot of drawbacks that limit its usage. In this study, shape memory nanocomposite was fabricated and characterised to determine the suitable material for aerospace structures. Three different loadings of nanoclay consisting of 1%, 3%, and 5% by weight percentage, three different loadings of Carbon Nanotube consisting of 0.5%, 1.0%, and 1.5% by weight percentage and hybrid loading of the same weight percentage were applied in preparation of the nanocomposites with epoxy as the polymer matrix. Single filler nanocomposite shows superior performance for 3% nanoclay and 1.0% Carbon Nanotube. For hybrid nanofiller, the glass transition temperature (Tg) of nanocomposite decreases as the nanofiller increase. The thermal properties of shape memory epoxy nanocomposite show a decrease in thermal degradation as the filler loading increase above 3% for nanoclay and 1.0% for Carbon Nanotube. For both tensile and flexural test at elevated and room temperature shows that the modulus increases as the hybrid filler increase and decrease as the loadings increase above 3% nanoclay and 1% Carbon Nanotube. The difference in modulus at elevated and room temperature shows the effect of molecular mobility above Tg as the shape memory epoxy is in the rubbery state. Thermal actuation of the hybrid nanocomposite shows increasing recovery rate as the nanofiller content increase. Generally, hybrid filler of 3% nanoclay and 1.0% Carbon Nanotube produces the best overall properties among the nanocomposites and has the potential be used for aerospace morphing structures. This study contributes to the development of hybrid nanofiller in shape memory polymer to understand the behaviour of shape memory epoxy nanocomposite.